Partial organic fertilizer replacing synthetic fertilizer reduces soil salinity, improves photosynthesis, and enhances the water-nitrogen use efficiency of maize (Zea maysl.) in arid regions - Yue Han; Zhanli Ma; Rui Chen; Yue Wen; Yonghui Liang; Jinzhu Zhang; Tehseen Javed; Wenhao Li; Zhenhua Wang (Agricultural Water Management)
Soil salinization severely threatens agricultural sustainability in arid regions, compromising crop productivity and resource-use efficiency. While organic amendments show promise for mitigating salinity stress, the optimal organic-to-synthetic fertilizer ratio remains undetermined in saline-alkaline agroecosystems. A two-year field experiment was conducted on saline-alkaline soil in southern Xinjiang, China, to assess soil properties, maize photosynthetic characteristics, and water-nitrogen use efficiency. Seven treatments were tested: no N fertilization (CK); 100 % synthetic N fertilizer (SF); and organic fertilizer substituting 20 %, 40 %, 60 %, 80 %, and 100 % of the synthetic N (OF20 %, OF40 %, OF60 %, OF80 %, and OF100 %, respectively) with all fertilized treatments receiving 300 kg N ha−1. To identify the optimal ratio of chemical-to-organic fertilizer, a comprehensive evaluation model was employed for multi-objective optimization analysis. Results showed that soil salinity and nitrate-N residue in the 0100 cm soil layer decreased by 1.12 %13.31 % and 14.06 %51.48 %, respectively, with increasing organic fertilizer substitution ratio. Additionally, maize photosynthetic performance and growth parameters exhibited an initial increase followed by a decline as organic substitution increased, peaking at the 20 % organic fertilizer substitution treatment. Compared to the SF treatment, the OF20 % treatment increased yield by 2.95 %8.03 %, crop water productivity by 2.98 %7.83 %, and nitrogen use efficiency by 1.85 %46.19 %. Regression analysis based on a multi-objective comprehensive evaluation model determined the optimal organic fertilizer substitution ratio to be 21.32 %. This enhancement resulted from improved soil physiochemical properties, enhanced photosynthetic capacity, and optimized resource utilization. These findings demonstrate that strategic partial organic substitution represents an effective strategy for sustainable intensification in salt-affected agricultural systems worldwide.